2007
DOI: 10.1007/s11738-006-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Podophyllotoxin content in Podophyllum hexandrum Royle plants of known age of seed origin and grown at a lower altitude

Abstract: Podophyllum hexandrum Royle, an important alpine herb, and a source of the highly valued aryltetralin-type lignan, podophyllotoxin, has been subjected to heavy collection from the wild due to ever increasing demand. The present study deals with an attempt to bring this plant under cultivation at a relatively lower altitude and to evaluate (1) various growth parameters including above and below ground biomass accumulation, net assimilation rate and relative growth rate, etc., and (2) podophyllotoxin content fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…These authors reported that increase in harvest index is due to the increase in biomass of the plant. Pandey et al (2007) reported variation in the harvest index in plants of different ages of P. hexandrum and reported maximum HI in plants of 5 year age, which produce higher biomass. The relative growth rate (RGR) also varied considerably amongst accessions of B. monnieri and also during different seasons (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors reported that increase in harvest index is due to the increase in biomass of the plant. Pandey et al (2007) reported variation in the harvest index in plants of different ages of P. hexandrum and reported maximum HI in plants of 5 year age, which produce higher biomass. The relative growth rate (RGR) also varied considerably amongst accessions of B. monnieri and also during different seasons (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the accessions, RGR was higher in BM14 in all the seasons and was found minimum in accession BM1 and BM7 during summer. Pandey et al (2007) reported the RGR as an index of biomass production in P. hexandrum. In this study, comparison of harvest index (HI) and relative growth rate was helpful for the selection of elite accessions (BM1 and BM7) and this study helped in identification of summer season when bacoside A levels are higher, which will help in developing management and conservation strategy for this important medicinal herb.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in podophyllotoxin content in different populations of P. peltatum and P. hexandrum can be ascribed to genotypic differences (Bastos et al, 1996;Moraes et al, 2000;Nadeem et al, 2007;Naik et al, 2010). The age of the plant has been reported to influence the toxin content in P. hexandrum (Sharma et al, 2000;Pandey et al, 2007). In this investigation, analyses were carried out on samples collected from wild populations; hence, the exact age of the sampled plants could not be ascertained.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of different lignans, particularly podophyllotoxin, in the rhizomes of P. hexandrum (Purohit et al, 1998;Sharma et al, 2000;Pandey et al, 2007;Nadeem et al, 2007;Naik et al, 2010;Kitchlu et al, 2011) and P. peltatum (Moraes et al, 2000;Canel et al, 2001;Zheljazkov et al, 2011) have been reported. Harvesting of this perrennating underground organ, for the analyses or commerce, adversely affects growth in subsequent years.…”
Section: Introductionmentioning
confidence: 99%
“…and Podophyllum peltatum L. (Berberidaceae), both of which have become endangered species as a result of over-collection. Besides the Berberidaceae members, PTOX is also found in other plant genera such as Linum, Juniperus, and Callitris (Fuss, 2003;Farkya et al, 2004;Pandey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%